2015
DOI: 10.1097/sap.0000000000000081
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Complications After Radiotherapy in Head and Neck Free Flap Reconstruction

Abstract: Radiotherapy as a risk factor for free flap failure has been widely debated. The purpose of this study was to investigate vascular complications in free flap surgery at a center advocating preoperative radiotherapy. On the basis of previous experimental studies, we also aimed to investigate temporal aspects of vascular complications in both arteries and veins. Furthermore, we aimed to study the effect of tissue plasminogen activator (tPA), because irradiated microvascular recipient vessels are associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
51
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 44 publications
2
51
2
Order By: Relevance
“…Other authors have reported total flap loss rates for head and neck reconstruction anywhere from 1.7 to 13.6%, with flap loss being more common in irradiated sites and late reconstructions. [24][25][26][27] Half of our cohort included irradiated patients; thus, these results are in line with those reported in the literature. Data regarding incidence intraoperative vasospasms, specifically in free flaps utilizing SVTS, appears to be limited in current literature.…”
Section: Discussionsupporting
confidence: 90%
“…Other authors have reported total flap loss rates for head and neck reconstruction anywhere from 1.7 to 13.6%, with flap loss being more common in irradiated sites and late reconstructions. [24][25][26][27] Half of our cohort included irradiated patients; thus, these results are in line with those reported in the literature. Data regarding incidence intraoperative vasospasms, specifically in free flaps utilizing SVTS, appears to be limited in current literature.…”
Section: Discussionsupporting
confidence: 90%
“…Efforts to explain radiation‐induced fibrosis, for example, by genetic variation have remained largely inconclusive. The authors have previously reported alterations in global gene expression in irradiated recipient vessels from free‐flap breast and head–neck reconstructions, but few studies have been able to describe gene expression patterns in irradiated breast adipose tissue. Furthermore, the effect of AFT on gene expression profiles in humans is largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…In a single institute analysis of 984 patients with 137 previously irradiated fields, Bourget et al determined radiation to be associated with a postoperative free flap complication rate of 47%, a reoperation rate of 22%, and a 28% infection rate. Tall et al, in a review of 283 cases with previous radiation, showed that total flap loss was more common in this group of patients, with flap failure increasing with time elapsed from surgery . In addition, they determined that flap salvage rates increased with the use of tissue plasminogen activator (tPA), further supporting the detrimental effects radiation has on the microvasculature.…”
Section: Discussionmentioning
confidence: 96%
“…22 This leads to hypovascular tissue with poor healing capability, with a recent meta-analysis of 24 studies that total flap loss was more common in this group of patients, with flap failure increasing with time elapsed from surgery. 23 In addition, they determined that flap salvage rates increased with the use of tissue plasminogen activator (tPA), further supporting the detrimental effects radiation has on the microvasculature. It is therefore imperative that extraordinary measures be taken in this group of patients to minimize post-operative morbidity.…”
Section: Discussionmentioning
confidence: 98%